Analisis Kualitas Pengembangan Four Tier Test untuk Mengetahui Profil Kemampuan Metakognisi Siswa Tingkat SMA Eks-Karesidenan Pati (UPEJ Unnes Physics Education Journal, 2020)
The research aims to develop a learning evaluation tool on Newton's Law material based on a four-level test to determine the quality of the instrument and the ability of the metacognition profile in students. The research design uses R&D (Research and Development) with the latest 4-D learning development model (define, design, develop, disseminate). The sampling experience was carried out at 3 state senior high schools in the ex-residency of Pati, namely SMAN 1 Juwana, SMAN 1 Kudus, and SMAN 1 Rembang with a total of 185 students as respondents. The results of the analysis at the small-scale test development stage resulted in an average validity of 87.26% by experts, a reliability value of 0.68 in the small-scale trial stage, and 0.74 in the large-scale trial. The difference power test on the small-scale examiner resulted in 16.67% of the total questions that could not be used for the next major testing stage. The results showed that for each indicator of metacognition abilities, 31% of students 'factual abilities were in the understanding category, 28% of students' conceptual abilities were categorized as understanding, 32% of students 'conceptual abilities were categorized as understanding, 14% of students' planning abilities were in the understanding category, In the research results for the ability indicator as high as 17%, and the evaluation indicator as much as 6% of students were categorized as understanding. Students in the category of understanding have the highest on the indicator of factual ability, while the lowest is on the indicator of evaluation ability. The research resulted that the four-tier test evaluation tool was feasible to be applied in high schools to be able to explore the profile of students' metacognitive abilities.